The Influence of the Labeling Effect on the Perception of Command Execution Delay in Gaming - Duy H. Nguyen; Peter A. Kara (Multimodal Technologies and Interaction)
Gaming is one of the largest industries of digital entertainment. Modern gaming software may be susceptible to command execution delay, which may be caused by various factors, such as insufficient rendering capabilities or limited network resources. At the time of writing this paper, the utilized advances in gaming are often accompanied by brief descriptions when communicated to the users. While such descriptions may be compressed into a couple of words, even a single word may impact user experience. Due to the cognitive bias induced by the labeling effect, the impact of such a word may actually be more significant than what the user genuinely perceives. In this paper, we investigate the influence of the labeling effect on the perception of command execution delay in gaming. We carried out a series of subjective tests to measure how the word “optimized” affects gaming experience. The test variables of our experiment were the added delay between command and execution, the speed of the game, and the label that was assigned to gaming sequences. The test participants were tasked to directly compare gaming sequences with the different labels assigned: “optimized” and “not optimized”. In every comparison, both sequences had the same objective characteristics; only the label differed. The experiment was conducted on single-input and continuous-input computer games that we developed for this research. The obtained results indicate that for both of these input types, the labeling effect has a statistically significant impact on perceived delay. Overall, more than 70% of the subjective ratings were affected by the assigned labels. Moreover, there is a strong correlation between the amount of delay and the effect of cognitive bias. The speed of the game also affected the obtained results, yet statistically significant differences were only measured between the slowest and the fastest gameplay.